2016
DOI: 10.1074/jbc.m115.661348
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Does Not Regulate Human Epidermal Keratinocyte Proliferation and Differentiation

Abstract: Hyaluronan (HA) is synthesized by three HA synthases (HAS1, HAS2, and HAS3) and secreted in the extracellular matrix. In human skin, large amounts of HA are found in the dermis. HA is also synthesized by keratinocytes in the epidermis, although its epidermal functions are not clearly identified yet. To investigate HA functions, we studied the effects of HA depletion on human keratinocyte physiology within in vitro reconstructed human epidermis. Inhibition of HA synthesis with 4-methylumbelliferone (4MU) did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 43 publications
3
34
0
2
Order By: Relevance
“…HA contributes to the control of cell proliferation, migration and differentiation (Sherman et al, 2015; Turley et al, 2016). A recent study showed that HA does not contribute to the growth and differentiation of human epidermal keratinocyte (Malaisse et al, 2016). Nevertheless, UDP-glucose induces HA synthesis in keratinocytes via P2Y14 receptor, STAT3 signaling and activation of hyaluronan synthase (HAS) promoter (Jokela et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…HA contributes to the control of cell proliferation, migration and differentiation (Sherman et al, 2015; Turley et al, 2016). A recent study showed that HA does not contribute to the growth and differentiation of human epidermal keratinocyte (Malaisse et al, 2016). Nevertheless, UDP-glucose induces HA synthesis in keratinocytes via P2Y14 receptor, STAT3 signaling and activation of hyaluronan synthase (HAS) promoter (Jokela et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, in one study, human keratinocytes were grown in monolayer and treated by HA of various MWs. No difference in proliferation index was observed in cells treated by low‐MW HA when compared with that of cells not treated by HA …”
Section: Effect Of Ha On Cell Proliferation and Differentiation In Vitromentioning
confidence: 88%
“…The stimulation effect on the proliferation of periodontal ligament cells was more obvious for synthesized HA of higher concentration . Other researchers reported that the proliferation of cells cultured with the addition of high‐MW HA was not affected when compared with that of cells cultured without HA . However, other studies showed that the cell proliferation was inhibited with the presence of high‐MW HA .…”
Section: Effect Of Ha On Cell Proliferation and Differentiation In Vitromentioning
confidence: 95%
See 2 more Smart Citations